A. A. Bogdanov’s model of socialism - Rumyantseva, Tatsiana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes the ideas of the revolution and socialism of the prominent Russian philosopher, scientist and thinker, who became an important character in the accomplishment of the revolutions of 1905 and 1917 – A. Bogdanov. It is shown that even at the beginning of the twentieth century he put forward a number of alternative Leninist ideas: about of the nature of October, Russia’s unpreparedness for socialism, about «military communism», as a result of militarization and economic dislocation. The analysis of ideas created by Bogdanov’s science of tectology made it possible to carry out a theoretical reconstruction of his model of socialism, within the framework of which the author outlined the main directions for the formation of fundamentally new social structures and developed a conceptual-categorical apparatus for comprehending the laws of motion and further renewal of the society. The importance of Bogdanov’s ideas was also revealed. It was shown that long before the well-known left-liberal theorists, he was able to identify the so-called. «Technocratic» roots of the Bolshevik state, to show the ineffectiveness of socialism, based on centralized management and planned production.
Keywords: A. A. Bogdanov; revolution in Russia; October 1917; military socialism; Proletcult; Utopia